Gut microbiome variation in pulmonary TB patients with diabetes or HIV comorbidities - Morgan, Portia Abena; Parbie, Prince Kofi; Ntiamoah, Desmond Opoku; Boadu, Augustine Asare; Asare, Prince; Lamptey, Ivy Naa Koshie; Gorman, Cecilia Nancy; Afreh, Emmanuel; Asante-Poku, Adwoa; Otchere, Isaac Darko; Aboagye, Sammy Yaw; Yeboah-Manu, Dorothy (Frontiers in Microbiomes, 2023)
Background The gut microbiota is known to play a critical role in shaping the host immunity, and metabolism and influences the onset and progression of both communicable and non-communicable diseases. This study assessed the gut microbiome of tuberculosis (TB) cases with diabetes mellitus (DM) or HIV comorbidities before anti-TB therapy and after the intensive phase anti-TB therapy. Methods Ninety cases comprising 60 TB-only, 23 TB-DM, 7 TB-HIV were recruited, among which 35 TB-only, 10 TB-DM, 5 TB-HIV were also sampled after 2 months of anti-TB treatment. Total gut microbiome was detected by 16S rRNA gene sequencing of DNA extracted from collected stool specimen. The taxonomic and functional diversity of the different groups were compared in addition to changes that could occur after 2 months antibiotics use. Results Compared to the healthy controls, the gut microbiome of all the TB cohorts was characterized by a significant decreased alpha diversity and significant compositional changes. All the three TB cohorts were enriched with inflammatory related microorganisms of the genera Escherichia-shigella, Streptococcus, Enterococcus and Erysipelatoclostridium with depletion in beneficial taxa of the genera Faecalibacterium, Bifidobacterium and Clostridium. In pairwise comparison with the healthy controls, the TB-only cohort were enriched with Streptococcus and Erysipelatoclostridium, the TB-DM enriched with Bacteroides, and TB-HIV enriched with Escherichia-shigella, Dialister and Erysipelatoclostridium. After the intensive phase anti-TB therapy, there was general enrichment of the genera Erysipelotrichaceae_UCG 003, Veillonella and Fusobacterium. Conclusion Our findings show a dysbiotic gut microbiome and associated upregulation of inflammation related microorganism in gut microbiome of TB individuals with or without comorbidity.